2021
DOI: 10.1016/j.asmr.2021.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Reoperation Rate at 2 Years Following Repair of Horizontal Cleavage Tears Using an All Suture-Based Technique: A Prospective, Multicenter Trial

Abstract: Purpose: This prospective, multicenter trial evaluates the clinical success (as measured by reoperation rates and improvements in patient-reported outcome measures) of using circumferential compression stitches with all-suture techniques for horizontal cleavage tears (HCTs) of the meniscus. Methods: Investigators enrolled 30 patients (mean age, 38.2 years; standard deviation, 11.1 years) aged 18 to 60 years with HCTs in the symptomatic compartment at 8 centers in the United States who underwent HCT repair with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Moreover, we confirm previous findings 4 demonstrating a trend toward meniscal repair—rather than meniscectomy—across all age groups. Such findings are likely a result of multiple advancements in the field of orthopaedics: appreciation of the adverse effect of meniscectomy, 18 improvement in all-inside meniscal repair devices, 15 and an increase in procedures performed by fellowship-trained specialists. 4,25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we confirm previous findings 4 demonstrating a trend toward meniscal repair—rather than meniscectomy—across all age groups. Such findings are likely a result of multiple advancements in the field of orthopaedics: appreciation of the adverse effect of meniscectomy, 18 improvement in all-inside meniscal repair devices, 15 and an increase in procedures performed by fellowship-trained specialists. 4,25…”
Section: Discussionmentioning
confidence: 99%
“…repair-rather than meniscectomy-across all age groups. Such findings are likely a result of multiple advancements in the field of orthopaedics: appreciation of the adverse effect of meniscectomy, 18 improvement in all-inside meniscal repair devices, 15 and an increase in procedures performed by fellowship-trained specialists. 4,25 To our knowledge, this study represents the first to describe the increased utilization of concurrent meniscal procedures in male patients as compared with female patients.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated the viability of using the Novostitch device (Smith & Nephew, Andover, MA) for HCTs. 22 The authors concluded that circumferential compression sutures using the Novostitch device (Smith & Nephew, Andover, MA) is appropriately indicated for repairing HCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright @ 2021 JPOSNA www.jposna.org change over time. Importantly, repair of the degenerative horizontal tear can yield good results, 15,16,17 evidenced by validated patient reported outcomes scores 15,16,17 and healing rates on follow-up arthroscopy. 16 Meniscus repair preserves meniscus tissue and is complementary to saucerization in the management the symptomatic discoid lateral meniscus where degenerative tears and instability are common as it addresses both tears and instability to improve load transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, meniscus repair has also been advocated over resection of horizontal cleavage tears to prevent excessive tibiofemoral contact pressures associated with complete resection. 14 Favorable outcomes have been shown in degenerative horizontal meniscal tear repairs, 15,16,17 and peripheral meniscus instability can be concurrently addressed with the same repair techniques by anchoring the meniscus to the joint capsule. 18 As tears are commonly associated with the discoid lateral meniscus, 2,19,20 especially in the degenerative horizontal cleavage configuration, 21,22 meniscal repair should be performed in conjunction with saucerization to create a functional meniscus for improved shock absorption and load transmission.…”
Section: Key Conceptsmentioning
confidence: 99%